CuFeS2at-FeS2 composite Fenton-like catalyst as well as preparation method and application thereof
By modifying natural pyrite, CuFeS2@FeS2 composite Fenton catalyst was prepared, which solved the problems of high energy and high cost when existing catalysts activate PMS and H2O2, and achieved efficient degradation of water organic pollutants and high-value utilization of pyrite resources.
Patent Information
- Application Number
- CN202411738808.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Existing catalysts require high energy input when activating PMS and H2O2, which is costly and has secondary pollution problems. The existing heterogeneous catalyst preparation process is complex and has high cost, making it difficult to achieve industrial application.
By modifying natural pyrite, CuFeS2@FeS2 composite Fenton catalyst was prepared, and the specific surface area and active site exposure of the catalyst were improved by using the intercalation of copper ions and the etching and pore expansion of citric acid.
The utilization rate of oxidant and the production of reactive oxygen species by catalysts has been significantly improved, the production cost of catalysts has been reduced, the high-value utilization of pyrite resources has been achieved, and an efficient water organic pollutant treatment plan has been provided.
Smart Images

Figure CN119549166A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of environmentally friendly functional materials and catalytic materials, and in particular to a CuFeS2@FeS2 composite Fenton-type catalyst and a preparation method and application thereof. Background Art
[0002] Advanced oxidation processes (AOPs) based on peroxymonosulfate (PMS) and hydrogen peroxide (H2O2) can generate more abundant reactive oxygen species (ROS), including sulfate radicals (SO4 ·- ), hydroxyl radical (·OH), superoxide radical (·O2 - ) and non-radical forms of singlet oxygen ( 1 O2), the high reactivity of these active oxygen species enables them to undergo rapid chain reactions with most organic pollutants in water, indiscriminately oxidizing these harmful substances into CO2, H2O or mineral salts, thereby achieving rapid degradation of different types of organic pollutants in water without causing secondary pollution.
[0003] Under normal circumstances, it is difficult for PMS and H2O2 to directly decompose and produce ROS. They need to be activated by external field energy or catalysts to achieve rapid mineralization of pollutants. At present, the methods for activating PMS and H2O2 mainly include ultraviolet activation, microwave activation, alkali activation, thermal activation, homogeneous catalyst activation based on transition metal ions, and heterogeneous catalyst activation based on transition metal oxides. Ultraviolet, microwave, alkali, and thermal activation all require continuous energy input, which makes their treatment cost too high and the reaction conditions harsh, making them difficult to promote industrially. Homogeneous catalyst activation will produce a large amount of sludge and pose the hazard of secondary pollution of heavy metals. Heterogeneous catalysts such as transition metal oxides have relatively excellent performance and lower cost compared to the above methods, and are currently the most promising direction for industrial application. However, the current heterogeneous catalysts are mainly based on synthesis, and the preparation process is usually complex and costly, which is the biggest obstacle to industrial application; and the reported catalysts are basically powders, which are difficult to achieve efficient separation from water bodies. If a fixed bed or fluidized bed device with continuous water inflow is used in the actual sewage treatment process, the efficiency will be greatly improved, which requires macroscopic granular catalysts.
[0004] Iron is the most common, cheap, easily available and non-toxic metal element. Natural pyrite is one of the most abundant metal sulfides on earth, with intact crystal form and environmental friendliness. The main use of pyrite is currently to produce sulfuric acid and sulfur, and the comprehensive utilization rate is low. The iron element in pyrite can activate PMS and H2O2 to produce a large number of free radicals, realize the degradation of organic pollutants, and use it in advanced oxidation catalysts to achieve high-value utilization of pyrite. In addition, natural pyrite itself is a macroscopic particle, which does not require further molding, reducing the molding cost required for traditional synthetic catalysts from powder to particles. However, natural pyrite particles are dense, low in specific surface area, and less exposed active sites. The conversion process of Fe(Ⅲ)→Fe(Ⅱ) in the catalytic process is slow, resulting in poor catalytic activity and low oxidant utilization in the actual pollutant degradation process. Therefore, it is necessary to modify natural pyrite to increase the number of its active sites and enhance its catalytic performance. Summary of the invention
[0005] In view of the above-mentioned shortcomings, the present invention provides a CuFeS2@FeS2 composite Fenton-like catalyst and its preparation method and application. The present invention utilizes the characteristics of natural pyrite particles that do not need further shaping and their own characteristic functional groups have good adsorption performance for copper ions. After simple crushing, Cu ions are impregnated and adsorbed, and then further calcined without oxygen to embed Cu ions into the pyrite lattice; at the same time, combined with the etching of citric acid on the surface of pyrite and the pore expansion effect during calcination, pyrite is prepared into a CuFeS2@FeS2 composite Fenton-like catalyst with a heterogeneous structure. Compared with natural pyrite, the composite material has a larger specific surface area and more exposed active sites. The incorporation of Cu enhances the redox cycle of Fe(Ⅱ) / Fe(Ⅲ), greatly improving the utilization rate of the catalyst for the oxidant. Compared with the heterogeneous Fenton-like catalysts prepared by chemical synthesis that have been reported so far, its preparation cost is significantly lower. This technological invention helps to realize the high-value utilization of pyrite resources, provides favorable assistance in the field of water organic pollutant treatment, and provides an innovative technical solution for the industrial application of advanced oxidation technology based on PMS / H2O2.
[0006] In order to achieve the above object, the present invention provides a method for preparing a CuFeS2@FeS2 composite Fenton-like catalyst, comprising the following steps:
[0007] S1. crushing, sieving, washing and drying natural pyrite in sequence to obtain natural pyrite particles; placing copper salt and citric acid in water and stirring to obtain a mixed solution;
[0008] S2, adding the natural pyrite particles to the mixed solution, evaporating part of the water after vacuum impregnation treatment, and then vacuum impregnating, repeating the evaporation-vacuum impregnation treatment to obtain a precursor;
[0009] S3. After filtering and drying the precursor, calcining it in an inert atmosphere, and then washing it with water, a granular CuFeS2@FeS2 composite Fenton-type catalyst is obtained.
[0010] It should be noted that the purpose of water washing in step S3 is to remove surface impurities and unstable substances.
[0011] Furthermore, in step S1, the purity of the natural pyrite is above 95%, and the average particle size of the natural pyrite is 1 to 6 mm.
[0012] Furthermore, natural pyrite has a purity of more than 98% regardless of its origin.
[0013] Furthermore, the average particle size of the natural pyrite is 2 to 4 mm.
[0014] Furthermore, in step S1, the molar ratio of the copper salt to the citric acid in the mixed solution is 1:1 to 1:4; the copper salt is one or both of copper nitrate and copper sulfate; and the citric acid and the copper salt are both of industrial grade.
[0015] Furthermore, in step S2, the molar ratio of the iron element in the natural pyrite particles to the copper salt and citric acid in the mixed solution is 25:2:2 to 25:5:20.
[0016] Furthermore, in step S2, the molar ratio of the iron element in the natural pyrite particles to the copper salt and citric acid in the mixed solution is 25:2:2 to 25:4:16.
[0017] Furthermore, in step S2, the vacuum impregnation treatment is performed for 4 to 8 hours, the drying temperature used for the evaporation is 60 to 80° C., and the evaporation-vacuum impregnation treatment is repeated 1 to 4 times.
[0018] Furthermore, the evaporation-vacuum impregnation treatment is repeated 1 to 3 times.
[0019] Furthermore, in step S3, the inert atmosphere includes any one of nitrogen and argon.
[0020] Furthermore, in step S3, the heating rate of the calcination treatment is 3-10°C / min, the temperature of the calcination treatment is 350-450°C, and the holding time of the calcination treatment is 60-120min.
[0021] Furthermore, in step S3, the temperature of the calcination treatment is 400-450° C., and the holding time of the calcination treatment is 60-90 min.
[0022] Based on the same inventive concept, the present invention also provides a CuFeS2@FeS2 composite Fenton-type catalyst prepared by the above preparation method.
[0023] Based on the same inventive concept, the present invention also provides the application of the CuFeS2@FeS2 composite Fenton catalyst prepared by the above preparation method in the treatment of organic wastewater, wherein the CuFeS2@FeS2 composite Fenton catalyst degrades organic pollutants in wastewater based on catalytically activated oxidants; wherein the oxidant includes at least one of hydrogen peroxide and peroxymonosulfate.
[0024] Furthermore, the organic pollutants include any one of surfactants, antibiotics, and dyes commonly found in water bodies; the surfactant includes sodium dodecylbenzene sulfonate; the antibiotic includes tetracycline hydrochloride; and the dye includes rhodamine B.
[0025] Beneficial effects of the present invention:
[0026] (1) Obvious raw material advantages: The present invention uses natural pyrite as the main raw material, and natural pyrite is abundant in nature and inexpensive. By modifying natural pyrite to prepare the CuFeS2@FeS2 composite catalyst, natural resources are fully utilized and the production cost of the catalyst is reduced. In addition, the copper salt and citric acid raw materials used in the preparation process are relatively common and easy to obtain. Compared with other synthetic catalysts, the composite catalyst of the present invention has obvious advantages in cost, which makes it possible to be used on a large scale in organic wastewater treatment. At the same time, this method also provides a new way to high-value utilization of natural pyrite, with good economic and environmental benefits.
[0027] (2) Good stability and recyclability: The pyrite-derived CuFeS2@FeS2 composite catalyst has a macroscopic granular structure and good stability. During the wastewater treatment process, the catalyst particles are not easily broken or dissolved, and can maintain their structural integrity and catalytic activity. At the same time, the granular catalyst can be recovered and reused by simple sedimentation, filtration or centrifugation. This not only reduces the loss of the catalyst and the cost of wastewater treatment, but also avoids the secondary pollution of the catalyst to the environment. After multiple recycling and use, the composite catalyst can still maintain a high catalytic activity and has good reusability.
[0028] (3) Excellent catalytic performance: The granular CuFeS2@FeS2 composite Fenton-like catalyst derived from natural pyrite of the present invention exhibits excellent catalytic performance in Fenton-like reactions. The present invention utilizes the good adsorption of pyrite to Cu ions, the etching of the pyrite surface by citrate, and the pore expansion effect during calcination to adsorb a large amount of Cu ions on the pyrite surface, embed Cu into the pyrite lattice through calcination, and form a honeycomb porous structure on the pyrite surface. The active sites of the catalyst are exposed, and the synergistic effect of Cu and Fe elements accelerates the redox cycle of Cu(Ⅰ) / Cu(Ⅱ) and Fe(Ⅱ) / Fe(Ⅲ), which can efficiently activate oxidants such as hydrogen peroxide and persulfate, and produce active oxygen species such as strongly oxidizing hydroxyl radicals and sulfate radicals. These active oxygen species can quickly degrade various difficult-to-degrade organic pollutants in wastewater, such as surfactant molecules in washing wastewater, antibiotic molecules in aquaculture wastewater, and dye molecules in printing and dyeing wastewater.
[0029] In summary, this patent uses natural pyrite, which is commonly found in nature, as raw material, and performs a simple modification treatment on it to form a granular CuFeS2@FeS2 composite Fenton-like catalyst with a heterogeneous structure. Compared with natural pyrite, this catalyst has a larger specific surface area and more exposed active sites. The incorporation of Cu enhances the redox cycle of Fe(Ⅱ) / Fe(Ⅲ), thereby greatly improving the utilization rate of the oxidant and the production of active oxygen species, and enhancing the catalytic degradation effect. Compared with the heterogeneous Fenton-like catalysts prepared by synthetic means that have been reported so far, it has lower preparation costs, better stability, and more convenient recycling. This technical invention helps to realize the high-value utilization of natural pyrite resources, provides favorable assistance to the field of water organic pollutant treatment, and provides innovative technical solutions for the industrial application of advanced oxidation technology based on PMS / H2O2. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 X-ray diffraction patterns of the granular CuFeS2@FeS2 composite catalyst of Example 1 of the present invention and the natural pyrite particles of Comparative Example 1;
[0031] Figure 2 These are scanning electron microscope images of the granular CuFeS2@FeS2 composite catalyst of Example 1 of the present invention and the natural pyrite particles of Comparative Example 1; wherein (a) is the natural pyrite particles of Comparative Example 1; and (b) is the granular CuFeS2@FeS2 composite catalyst of Example 1. DETAILED DESCRIPTION
[0032] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.
[0033] The comparative examples and embodiments of the present invention use natural pyrite from different regions of my country as raw materials, and the purity thereof is shown in Table 1. The copper salt used in the embodiments is one or a combination of copper nitrate and copper sulfate, and the citric acid and copper salt are both industrial grade.
[0034] Table 1:
[0035]
[0036] The organic pollutant degradation experiments of the various embodiments and comparative examples of the present invention are all completed using a continuous catalytic degradation experimental device. The main body of the device is a cylindrical fixed bed, which is filled with quartz sand as an inert filler on the top and bottom, and a catalyst particle bed of a determined height in the middle; a constant-flow peristaltic pump is used to transport organic polluted wastewater (containing oxidant) with a concentration of C0 to the fixed bed for catalytic degradation reaction, and the effluent after passing through the fixed bed reactor is collected to detect changes in pollutant concentration. The temperature of the fixed bed and the wastewater are controlled separately by a temperature control device to ensure the accuracy and stability of the experimental data. After the set experimental time, the concentration of organic pollutants in the effluent (C t The catalytic performance was evaluated by the degradation rate (Formula 1).
[0037] Degradation rate = (C0-C t ) / C0×100% Formula (1)
[0038] Example 1
[0039] The natural pyrite used in this embodiment is produced in Gansu, with a purity of 98%. Industrial-grade copper nitrate trihydrate and industrial-grade citric acid monohydrate are used. The specific implementation process includes:
[0040] (1) crushing natural pyrite, sieving the crushed pyrite particles, screening out pyrite particles with a particle size of 3±1 mm, washing the sieved pyrite particles in ultrapure water to remove surface impurities, and then drying them in an oven for later use.
[0041] (2) Copper nitrate trihydrate and citric acid monohydrate are placed in a beaker filled with ultrapure water and stirred thoroughly to dissolve them to form a mixed solution, wherein the molar ratio of copper salt to citric acid in the mixed solution is 1:2.
[0042] (3) Adding natural pyrite particles to the mixed solution, the molar ratio of iron element to copper salt and citric acid in the natural pyrite particles is 25:2:4, and then vacuum impregnation is performed for 5 hours. The impregnated solution is placed in an oven at 60°C to evaporate part of the water, and then vacuum impregnation is performed again; repeating the evaporation-vacuum impregnation steps once to obtain a precursor.
[0043] (4) The precursor was filtered, dried, and placed in a tube furnace for calcination in an inert atmosphere at a heating rate of 5°C / min within a calcination temperature range of 400°C for 60 min. The precursor was taken out and washed in ultrapure water to remove surface impurities and unstable substances to obtain a granular CuFeS2@FeS2 composite Fenton-like catalyst. The granular CuFeS2@FeS2 composite Fenton-like catalyst was analyzed by X-ray diffraction and scanning electron microscopy. The results are as follows: Figures 1-2 shown.
[0044] Two equal amounts of granular CuFeS2@FeS2 composite catalyst were taken and filled into two fixed beds. Taking tetracycline hydrochloride as the target pollutant (concentration of 30 mg / L), PMS and H2O2 were added to the two tetracycline hydrochloride solutions respectively. M is defined as the ratio of the mass of the treated wastewater to the mass of the catalyst used. Taking PMS as the oxidant, when M is 100, the degradation rate of tetracycline hydrochloride is 91%, and when M is 2000, it still retains a degradation rate of 79%. Taking H2O2 as the oxidant, when M is 100, the degradation rate of tetracycline hydrochloride is 88%, and when M is 2000, it still retains a degradation rate of 74%, see Table 2 for details. The CuFeS2@FeS2 composite catalyst can activate both PMS and H2O2, and has excellent degradation performance and long-term catalytic stability for tetracycline hydrochloride.
[0045] Example 2
[0046] The natural pyrite used in this embodiment is produced in Anhui, with a purity of 96%. Industrial-grade copper sulfate pentahydrate and industrial-grade citric acid monohydrate are used. The specific implementation process includes:
[0047] (1) crushing natural pyrite, sieving the crushed pyrite particles, screening out pyrite particles with a particle size of 5±1 mm, washing the sieved pyrite particles in ultrapure water to remove surface impurities, and then drying them in an oven for later use.
[0048] (2) Copper sulfate pentahydrate and citric acid monohydrate are placed in a beaker filled with ultrapure water and stirred thoroughly to dissolve them to form a mixed solution, wherein the molar ratio of copper salt to citric acid in the mixed solution is 1:3.
[0049] (3) Adding natural pyrite particles to the mixed solution, wherein the molar ratio of iron to copper salt and citric acid in the natural pyrite particles is 25:4:16, and then vacuum impregnation is performed for 6 hours. The impregnated solution is placed in an oven at 60°C, and after evaporating part of the water, vacuum impregnation is performed again. Repeating the evaporation-vacuum impregnation steps 3 times, a precursor is obtained.
[0050] (4) The precursor is filtered, dried, placed in a tubular furnace, and calcined in an inert atmosphere at a heating rate of 10°C / min within a calcination temperature range of 450°C for 90 min. The precursor is taken out and washed in ultrapure water to remove surface impurities and unstable substances, thereby obtaining a granular CuFeS2@FeS2 composite Fenton-like catalyst.
[0051] Two equal amounts of granular CuFeS2@FeS2 composite catalyst were taken and filled into two fixed beds. Taking sodium dodecylbenzene sulfonate as the target pollutant (concentration of 40 mg / L), PMS and H2O2 were added to the two sodium dodecylbenzene sulfonate solutions respectively. M is defined as the ratio of the mass of the treated wastewater to the mass of the catalyst used. Taking PMS as the oxidant, when M is 100, the degradation rate of sodium dodecylbenzene sulfonate is 84%, and when M is 2000, it still retains a degradation rate of 72%. Taking H2O2 as the oxidant, when M is 100, the degradation rate of sodium dodecylbenzene sulfonate is 81%, and when M is 2000, it still retains a degradation rate of 69%, see Table 2 for details. CuFeS2@FeS2 composite catalyst can activate both PMS and H2O2, and has excellent degradation performance and long-term catalytic stability for sodium dodecylbenzene sulfonate.
[0052] Example 3
[0053] The natural pyrite used in this embodiment is produced in Guangdong, with a purity of 95%. Industrial-grade copper nitrate trihydrate and industrial-grade citric acid monohydrate are used. The specific implementation process includes:
[0054] (1) crushing natural pyrite, sieving the crushed pyrite particles, screening out pyrite particles with a particle size of 6±1 mm, washing the sieved pyrite particles in ultrapure water to remove surface impurities, and then drying them in an oven for later use.
[0055] (2) Copper nitrate trihydrate and citric acid monohydrate are placed in a beaker filled with ultrapure water and stirred thoroughly to dissolve them to form a mixed solution, wherein the molar ratio of copper salt to citric acid in the mixed solution is 1:1.5.
[0056] (3) Adding natural pyrite particles to the mixed solution, the molar ratio of iron element to copper salt and citric acid in the natural pyrite particles is 25:3:4.5, and then vacuum impregnation is performed for 7 hours. The impregnated solution is placed in an oven at 80°C to evaporate part of the water, and then vacuum impregnation is performed again; repeating the evaporation-vacuum impregnation steps twice to obtain a precursor.
[0057] (4) The precursor is filtered, dried, placed in a tubular furnace, and calcined in an inert atmosphere at a heating rate of 5°C / min within a calcination temperature range of 350°C for 120 min. The precursor is taken out and washed in ultrapure water to remove surface impurities and unstable substances, thereby obtaining a granular CuFeS2@FeS2 composite Fenton-like catalyst.
[0058] Two equal amounts of granular CuFeS2@FeS2 composite catalyst were taken and filled into two fixed beds. Rhodamine B was taken as the target pollutant (concentration was 20 mg / L), and PMS and H2O2 were added to the two Rhodamine B solutions respectively. M is defined as the ratio of the mass of the treated wastewater to the mass of the catalyst used. With PMS as the oxidant, when M was 100, the degradation rate of Rhodamine B was 98%, and when M was 2000, it still maintained a degradation rate of 86%. With H2O2 as the oxidant, when M was 100, the degradation rate of the catalyst tetracycline hydrochloride was 96%, and when M was 2000, it still maintained a degradation rate of 80%, see Table 2 for details. The CuFeS2@FeS2 composite catalyst can activate PMS and H2O2, and has excellent degradation performance and long-term catalytic stability for Rhodamine B.
[0059] Comparative Example 1
[0060] The natural pyrite used in this comparative example is produced in Gansu, with a purity of 98%. The specific implementation process includes:
[0061] First, the natural pyrite is crushed and sieved, and the pyrite particles with a particle size of 3±1 mm are screened, washed with ultrapure water to remove surface impurities and unstable components, and placed in an oven for drying to obtain pyrite particles for use. Among them, the pyrite particles are subjected to X-ray diffraction and scanning electron microscopy analysis, and the results are as follows Figures 1-2 As shown. The catalytic degradation process is the same as in Example 1. Define M as the ratio of the mass of treated wastewater to the mass of the catalyst used. Taking PMS as the oxidant, when M is 100, the degradation rate of tetracycline hydrochloride is 59%, and when M is 2000, the degradation rate drops to 34%. Taking H2O2 as the oxidant, when M is 100, the degradation rate of tetracycline hydrochloride is 54%, and when M is 2000, the degradation rate drops to 32%, see Table 2 for details. Natural pyrite can activate both PMS and H2O2, but the catalytic degradation performance of pyrite on tetracycline hydrochloride is poor.
[0062] Comparative Example 2
[0063] The natural pyrite used in this comparative example is produced in Gansu, with a purity of 98.00%. Industrial-grade copper nitrate trihydrate and industrial-grade citric acid monohydrate are used. The specific implementation process includes:
[0064] (1) crushing natural pyrite, sieving the crushed pyrite particles, screening out pyrite particles with a particle size of 3±1 mm, washing the sieved pyrite particles in ultrapure water to remove surface impurities, and then drying them in an oven for later use.
[0065] (2) Copper nitrate trihydrate and citric acid monohydrate are placed in a beaker filled with ultrapure water and stirred thoroughly to dissolve them to form a mixed solution, wherein the molar ratio of copper salt to citric acid in the mixed solution is 1:2.
[0066] (3) adding natural pyrite particles to the mixed solution, wherein the molar ratio of the iron element in the natural pyrite particles to the copper salt and the citric acid is 25:2:4, and then vacuum impregnation is performed for 5 hours without repeated impregnation to obtain a precursor.
[0067] (4) The precursor is filtered, dried, placed in a tubular furnace, and calcined in an inert atmosphere at a heating rate of 5°C / min within a calcination temperature range of 400°C for 60 min. The precursor is taken out and washed in ultrapure water to remove surface impurities and unstable substances, thereby obtaining a granular CuFeS2@FeS2 composite Fenton-like catalyst.
[0068] Two equal amounts of granular CuFeS2@FeS2 composite catalyst were taken and filled into two fixed beds. Taking tetracycline hydrochloride as the target pollutant (concentration of 30 mg / L), PMS and H2O2 were added to the two tetracycline hydrochloride solutions respectively. M is defined as the ratio of the mass of the treated wastewater to the mass of the catalyst used. Taking PMS as the oxidant, when M is 100, the degradation rate of tetracycline hydrochloride is 76%, and when M is 2000, the degradation rate drops to 60%. Taking H2O2 as the oxidant, when M is 100, the degradation rate of tetracycline hydrochloride is 72%, and when M is 2000, the degradation rate drops to 54%, see Table 2 for details. CuFeS2@FeS2 composite catalyst can activate PMS and H2O2. Since only one impregnation was performed, the Cu element loading is low, and the catalyst has a general degradation effect on tetracycline hydrochloride.
[0069] Table 2:
[0070]
[0071]
[0072] Result analysis:
[0073] Table 2 above is a comparison of the performance of the Fenton-like catalysts of various comparative examples and embodiments in catalyzing the degradation of organic matter by PMS / H2O2.
[0074] Comparative Example 1 is unmodified natural pyrite particles as PMS and H2O2 catalysts, tetracycline hydrochloride as the target pollutant, and catalytic degradation experiments are carried out to evaluate its catalytic performance. It can be seen that natural pyrite can activate PMS and H2O2, but its catalytic degradation performance and cycle stability of pollutants are poor. In Example 1, when the granular CuFeS2@FeS2 composite catalyst is M=100, when PMS and H2O2 are used as oxidants, the degradation rates of tetracycline hydrochloride are 91% and 88% respectively, and when M=2000, the degradation rates of tetracycline hydrochloride are 79% and 74% respectively, which are significantly higher than the effect of Comparative Example 1. The CuFeS2@FeS2 composite catalyst of Example 1 of the present application has a higher utilization rate of PMS and H2O2 than Comparative Example 1, and has stronger catalytic performance and cycle stability.
[0075] Comparative Example 2 is a granular CuFeS2@FeS2 composite catalyst prepared by calcination after one impregnation. Due to the limited adsorption performance of pyrite for Cu ions, the Cu element loading in the catalyst is small, and the catalytic degradation performance is significantly worse than that of Example 1. After Example 1 is heated up after impregnation and part of the water is evaporated, the Cu ion concentration is further improved, and the vacuum impregnation step is repeated to continue to adsorb Cu ions, so that the Cu element loading is greatly improved. However, the impregnation step should not be repeated too much. Too many impregnation times will cause the loading layer to be too dense, resulting in the inner layer active sites being covered, and a good catalytic effect cannot be achieved.
[0076] Depend on Figure 1 and Figure 2 It can be seen that after modification, peaks of FeS2 and CuFeS2 appeared on the surface of the granular CuFeS2@FeS2 composite catalyst of the present application, and a honeycomb structure appeared on the surface of the catalyst, which increased the number of active sites, making it easier for the oxidant to be adsorbed on the catalyst surface and further decomposed into a large number of active oxygen species, thereby achieving rapid degradation of organic pollutants; while in Comparative Example 1, the surface of natural pyrite was dense and smooth, with few active sites exposed, less contact between the active sites and the oxidant, and poor catalytic performance.
[0077] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing a CuFeS2@FeS2 composite Fenton-type catalyst, characterized in that: The following steps are involved: S1. crushing, sieving, washing and drying natural pyrite in sequence to obtain natural pyrite particles; placing copper salt and citric acid in water and stirring to obtain a mixed solution; S2, adding the natural pyrite particles to the mixed solution, evaporating part of the water after vacuum impregnation treatment, and then vacuum impregnating, repeating the above evaporation-vacuum impregnation treatment to obtain a precursor; S3. After filtering and drying the precursor, calcining it in an inert atmosphere, and then washing it with water, a granular CuFeS2@FeS2 composite Fenton-type catalyst is obtained.
2. The method for preparing the CuFeS2@FeS2 composite Fenton-type catalyst according to claim 1, characterized in that: In step S1, the purity of the natural pyrite is above 95%, and the average particle size of the natural pyrite is 1 to 6 mm.
3. The method for preparing the CuFeS2@FeS2 composite Fenton-type catalyst according to claim 1, characterized in that: In step S1, the molar ratio of the copper salt to the citric acid in the mixed solution is 1:1 to 1:4; the copper salt is one or both of copper nitrate and copper sulfate; and the citric acid and the copper salt are both of industrial grade.
4. The method for preparing the CuFeS2@FeS2 composite Fenton-type catalyst according to claim 1, characterized in that: In step S2, the molar ratio of the iron element in the natural pyrite particles to the copper salt and citric acid in the mixed solution is 25:2:2 to 25:5:
20.
5. The method for preparing the CuFeS2@FeS2 composite Fenton-type catalyst according to claim 1, characterized in that: In step S2, the vacuum impregnation treatment is performed for 4 to 8 hours, the evaporation temperature is 60 to 80°C, and the evaporation-vacuum impregnation treatment is repeated 1 to 4 times.
6. The method for preparing the CuFeS2@FeS2 composite Fenton-type catalyst according to claim 1, characterized in that: In step S3, the inert atmosphere includes any one of nitrogen and argon.
7. The method for preparing the CuFeS2@FeS2 composite Fenton-type catalyst according to claim 1, characterized in that: In step S3, the heating rate of the calcination treatment is 3-10°C / min, the temperature of the calcination treatment is 350-450°C, and the holding time of the calcination treatment is 60-120min.
8. A CuFeS2@FeS2 composite Fenton-type catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the CuFeS2@FeS2 composite Fenton-type catalyst prepared by the preparation method according to any one of claims 1 to 7 or the CuFeS2@FeS2 composite Fenton-type catalyst according to claim 8 in sewage treatment, characterized in that: The CuFeS2@FeS2 composite Fenton-like catalyst degrades organic pollutants in sewage based on catalytic activation of an oxidant; wherein the oxidant includes at least one of hydrogen peroxide and peroxymonosulfate.
10. The use according to claim 9, characterized in that: The organic pollutants include any one of common surfactants, antibiotics, and dyes in water bodies; the surfactant includes sodium dodecylbenzene sulfonate; the antibiotic includes tetracycline hydrochloride; and the dye includes rhodamine B.
Citation Information
Patent Citations
Method for removing antibiotics in water body by using chalcopyrite to activate percarbonate
CN113402008A
Manufacture of positive pole active substance for organic electrolyte battery
JP1984171466A
Preparation method of mercury removal material
US20230068024A1